ANALISIS KANDUNGAN KADMIUM (Cd) DAN SENG (Zn) DALAM KUBIS BUNGA (Brassica oleracea var. botrytis L) DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Deski Pahdinol; Amrin Amrin; Edi Nasra (Jurnal Periodic Jurusan Kimia UNP, 2013)
Flowers cabbage (Brassica oleracea var. botrytis L) is an important and widely grown vegetable in many places. Soil as the growth of vegetables such as flowers cabbage can be contaminated media by harmful substances, such as heavy metals like cadmium (Cd) and zinc (Zn). Analysis of cadmium and zinc contents in flowers cabbage in the Koto Baru in Tanah Datar and Padang Lua in Agam by Atomic Absorption Spectrophotometry has been done. This study aims to determine the content of cadmium (Cd) and zinc (Zn) in flowers cabbage and to know what kind of a good solvent on the analysis of the content of cadmium (Cd) and zinc (Zn) in flowers cabbage by Atomic Absorption Spectrophotometry. This study uses a wet destruction, where the destruction process done with some variation of the solvent variation: HClO4 p.a, HNO3 p.a and HNO3-HClO4 mixture (4:1). Research results showed that local flowers cabbage in Koto Baru Tanah Datar and Padang Lua Agam is still below the safety limit but still have to watch out for. Good solvent for analysis of Cd metal content in the sample flowers cabbage  for Koto Baru area of ​​Tanah Datar is HNO3-HClO4 mixture (4:1) for a Padang Lua, Agam is HClO4 p.a good solvent for analysis of Zn metal content in the sample flowers cabbage for Koto Baru area of ​​Tanah Datar and Agam, Padang Lua is HNO3-HClO4 mixture.